C‐Dimethylated Flavones as Possible Potential Anti‐Tubercular and Anticancer Agents. Issue 4 (29th March 2023) - Bollikolla, Hari Babu; Anandam, Rambabu; Chinnam, Sampath; Varala, Ravi; Khandapu, Bala Murali Krishna; Kapavarapu, Ravikumar; Syed, Khasim Sharif; Dubasi, Narasimhaswamy; Syed, Mastan Ali
Abstract: The present investigation describes an intramolecular Oxa‐Michael addition of penta‐substituted phenols to the enone of the tether in the presence of iodine as the oxidizing agent. Ten C‐ Dimethylated flavones with moderate to good yields (10a –j, 60–89 %) were isolated by heating the corresponding C ‐dimethylated chalcones using iodine in DMSO. Using the Microplate Alamar Blue test (MABA) technique, the drugs′ quantitative drug susceptibility against the H37Rv strain of replicating Mycobacterium TB was determined. The sensitivity of two of the developed compounds (10e, 10h ) was up to 6.25 g/mL. The human lung adenocarcinoma cell lines (A549) were used in the anticancer study, which was carried out using the MTT cell proliferation assay. In A549 cell lines, four flavones demonstrated anticancer activity with IC50 values between 39 and 48 μM. The C ‐dimethylated flavones, 10b (3, 4‐dimethoxy), 10c (2, 3, 4‐trimethoxy), 10e ( p‐ fluoro) and 10 g ( N ‐methyl indole) substitutions on ring 'B' showed good anticancer activity with IC50 values 39.17, 39.21, 48.43 and 43.48 μM, respectively. The compounds 10b, 10c, 10d, 10e, and 10i had improved binding and interaction profiles among all the compounds examined during the current In Silico research, as shown by the docking simulations against two targets EGFR and MTB MurI. Abstract :